Quality of Life Assessment for Patients with Colorectal Cancer - AlAttar, wafaa (Iraqi National Journal of Nursing Specialties, 2005)
Abstract A descriptive study to assess the quality of life (QOL) for patients with colorectal cancer. The study was conducted from Baghdad Teaching Hospital, Al-Yarmouk Teaching Hospital and Radiation Hospital and Nuclear medicine for the period from 1st July/2004 to 1st September/2004. The sample selected by purposive random of (50) patients diagnosed with colorectal cancer and all of them who were under chemotherapy treatment. A questionnaire was prepared for the purpose of the study and comprised of three parts including: 1- Socio-demographical characteristics. 2- Clinical characteristics. 3- and QOL assessment for patients with colorectal cancer, consist of (30) items. The questionnaire was tested for its validity and reliability. Data were analyzed by using frequency, percentage, mean of score and Chi-square. The results of the study indicated that the QOL for patients were greatly effected during (10) items such as they have trouble in walking and mobility and also they feel pain, tired and weakness… etc. Therefore was recommended education program to be developed and implemented of patients with colorectal cancer who were under chemotherapy treatment.